Aducanumab and lecanemab - two novel antibodies against pathologic species of amyloid beta in the treatment of Alzheimer's disease - Jakub Wojcieszak (Polish Pharmaceutical Society, 2023)
Alzheimer's disease (AD) is the most common cause of dementia worldwide. According to the widely accepted theory, it is caused by neurodegeneration initiated by the deposition of a pathological protein, amyloid β, in the brain. Amyloid β can aggregate to form neurotoxic oligomers, which also contribute to other pathological changes: hyperphosphorylation of the Tau protein and its deposition in the form of neurofibrillary tangles, and neuroinflammation. Despite the considerable efforts of the scientific community and pharmaceutical companies, no new drug against AD has been registered over the last decades. In addition, the four drugs currently available in Europe act only symptomatically and do not inhibit the progression of pathophysiological changes that cause the disease. Over the past two years, the U.S. Food and Drug Administration (FDA) has approved two new drugs modifying the course of Alzheimer's disease - monoclonal antibodies against toxic forms of amyloid β: aducanumab and lecanemab. Both drugs have been approved using an accelerated pathway based on their effectiveness in reducing amyloid content in patients' brains. This caused controversy among the scientific community because these preparations were approved based on surrogate endpoints of clinical trials whose primary endpoints, i.e. a significant slowing of the progression of dementia, were not achieved, and therefore the clinical efficacy of these antibodies has not been unequivocally demonstrated. Safety of the therapy brings another concerns. In studies of both medicines, changes in the brains of patients, such as edema, micro- and macrohaemorrhages, were observed. At present, both antibodies have not received a positive opinion from the European Medicines Agency (EMA). Since it is believed that passive immunization with humanized monoclonal antibodies may be a new and groundbreaking form of AD therapy, the research done on aducanumab and lecanemab deserves attention. The paper discusses in detail data from preclinical and clinical studies published by the manufacturers of both preparations.